2005
DOI: 10.1029/2004ja010986
|View full text |Cite
|
Sign up to set email alerts
|

Overlap of the plasmasphere and ring current: Relation to subauroral ionospheric heating

Abstract: [1] The overlap of the ring current with the outer plasmasphere is thought to play a major role in storm-time related increases in the subauroral ambient topside electron temperature. Instabilities generated within the overlap region, Coulomb collisions of plasmaspheric electrons with the ring current ions, and charge exchange are all thought to work either individually or together to generate a downward heat flux into the ionosphere to produce the increase in temperature. Analysis of IMAGE two-dimensional rin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 44 publications
1
53
0
Order By: Relevance
“…EMIC waves are preferentially generated in regions where hot anisotropic H + and cold dense ion populations spatially overlap [e.g., Jordanova et al, 2001;Pickett et al, 2010;Zhang et al, 2011]. In the terrestrial magnetosphere, these ion populations can commonly be found where the ring current overlaps the plasmasphere or plasmaspheric plumes [Gurgiolo et al, 2005;Thorne, 2010].…”
Section: Introductionmentioning
confidence: 99%
“…EMIC waves are preferentially generated in regions where hot anisotropic H + and cold dense ion populations spatially overlap [e.g., Jordanova et al, 2001;Pickett et al, 2010;Zhang et al, 2011]. In the terrestrial magnetosphere, these ion populations can commonly be found where the ring current overlaps the plasmasphere or plasmaspheric plumes [Gurgiolo et al, 2005;Thorne, 2010].…”
Section: Introductionmentioning
confidence: 99%
“…A quite sophisticated approach is the use of data quality flags to eliminate the Earth's shadow region, the auroral emission, and the seams between the fields-of-view of the three EUV cameras from the analysis (Galvan et al 2008). Not doing so results in erroneous contributions to the solution in the subsequent image inversion process (Gurgiolo et al 2005).…”
Section: Removal Of Noise and Instrument Artifactsmentioning
confidence: 99%
“…Subtraction of the image background largely eliminates the adverse effects of straylight in the EUV instrument and facilitates further image processing (Gurgiolo et al 2005;Gallagher and Adrian 2007;Galvan et al 2008). A quite sophisticated approach is the use of data quality flags to eliminate the Earth's shadow region, the auroral emission, and the seams between the fields-of-view of the three EUV cameras from the analysis (Galvan et al 2008).…”
Section: Removal Of Noise and Instrument Artifactsmentioning
confidence: 99%
See 1 more Smart Citation
“…A range of diverging field strengths exists (Karlsson et al, 1998); very strong fields and the associated drifts might produce stable auroral red arcs as a consequence of the ion and electron heating due to ion-neutral collisions (Hoch and Lemaire, 1974;Foster et al, 1994;Moffett et al, 1998). SAPS and SAID have substantial effects on the plasmasphere and the ring current, and on the overall configuration of the inner magnetosphere (Foster et al, 1994;Ober et al, 1997;De Keyser, 1999;Goldstein et al, 2003Goldstein et al, , 2005Gurgiolo et al, 2005;Foster et al, 2007;Voiculescu and Roth, 2008).…”
Section: Discussionmentioning
confidence: 99%